Dampak Dehidrasi Saat Masa Kehamilan - Erlicha Paramitha Maryanto (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Water is important for a person and has a function to maintain cell hemostasis. The composition of fluids in the body changes during pregnancy to support the growth and development of the fetus in the womb. Physiological conditions experienced by pregnant women can affect the balance of body fluids which will affect the hydration status of pregnant women. In Indonesia, it is found that 57.1% of pregnant women are dehydrated. Dehydration is a condition where the body loses more fluids than the fluids intake. This study used a literature study method with the keywords "pregnancy", "dehydration", "hydration state”. The effects of dehydration during pregnancy include impaired fetal growth and development, decreased amniotic volume, urinary tract infections, and constipation. Prevention of lack of fluids must be done by consuming enough water, namely 3 L / day, which comes from drinks or foods with high humidity and meets the needs of nutritional intake.